Analysis of the range of acceleration for an accelerometer with extended beams - Ramon Cabello; Margarita Tecpoyotl; Jose Gerardo Vera; Alfonso Torres; Pedro Vargas; Svetlana Koshevaya (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The elastic behaviour of a system can be determined by an analysis of stresses. The stress generated in the element loaded of an accelerometer is of interest here. In these devices, the suspension beams are the elements subjected to greater stresses, as they support the mass. The stress that they can support is limited by the elastic limit of the material. Based on this analysis, the operating conditions to prevent permanent deformations are determined. The analysis is focused on the acceleration applied to the accelerometer because this parameter increases considerably the stresses in the device. A relationship between normal stress and gravity applied is obtained. This equation is used in order to avoid exceeding the elastic limit, during the accelerometer operation. This fact determines the acceleration range supported by the device. In the literature, studies about the physics and modelling of accelerometers are performed. However, about the specific acceleration of operation which they are subjected, information about its determination is not provided. In this paper, the analysis is realized considering a Conventional Capacitive Accelerometer (CCA) and a Capacitive Accelerometer with Extended Beams (CAEB), particularly, on the normal stress. When a range of acceleration values are applied, normal stress occur which must not exceed the elastic limit of the material, as it was mentioned before. The Matlab code used to calculate this relationship is given in Appendix A.